(untitled) (Global Journal of Science Frontier Research, 2017)
The human is facing two big problems: The weather climate changes and energy crisis. There are a lot of causes to make above issues. One of them is a phenomenon of Greenhouse Gas emissions from industrial activities and humans. In my researching field, the author concentrates on studying how to reduce the Greenhouse Gas emissions from transportation ships using studying the Marginal Abatement Cost (MAC) curves applying to all ships. In purpose of researching that creates green shipping in the changeable climate condition nowadays.